2021
DOI: 10.3390/ma14102591
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Proton Exchange Membrane Failure and Mitigation Strategies

Abstract: Proton exchange membrane (PEM) is critical for the efficient, reliable and safe operation of proton exchange membrane fuel cells (PEMFC). The lifetime of PEM is the main factor restricting the commercialization of PEMFC. The complexity of operating conditions, such as open-circuit/idling, dynamic load and startup-shutdown under automotive conditions, on PEMFC will cause the mechanical and chemical degradation of PEM and affect the service life of PEMFC. In order to understand the degradation behavior and durab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 79 publications
(109 reference statements)
0
28
0
Order By: Relevance
“…The hydrogen permeation could commonly indicate the degree of membrane mechanical durability. [ 35 ]. As shown in Figure 6 , the membranes after dynamic mechanical aging (by pressure-loaded blistering time for 10 min) revealed rapid hydrogen permeability compared with the original membranes, which presumably suggested that the dynamic mechanical aging caused chemical degradation and microstructure mechanical damage of the membranes.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrogen permeation could commonly indicate the degree of membrane mechanical durability. [ 35 ]. As shown in Figure 6 , the membranes after dynamic mechanical aging (by pressure-loaded blistering time for 10 min) revealed rapid hydrogen permeability compared with the original membranes, which presumably suggested that the dynamic mechanical aging caused chemical degradation and microstructure mechanical damage of the membranes.…”
Section: Resultsmentioning
confidence: 99%
“…At the cathode, hydrogen peroxide is formed when oxygen is reduced through the two-electron pathway [ 28 ]. When hydrogen peroxide decomposes and reacts with metal ions (e.g., Fe 2+ , Cu 2+ , and Cr 3+ ) formed during the degradation of other components in the fuel cell (e.g., bipolar plate and sealing materials), intermediate products, such as hydroxyl radicals with strong oxidative characteristics are produced [ 29 ]. These radicals attack the polymer chain, causing defragmentation, unzipping, and thinning of the membrane [ 30 , 31 ].…”
Section: Functional Requirementsmentioning
confidence: 99%
“…A strategy to mitigate such radical attacks consists of the incorporation of radical scavengers. For example, the introduction of metal cations, such as Ce 4+ and Mn 2+ , or their oxides, including CeO 2 and MnO 2 , revealed to be effective in mitigating the chemical degradation of PFSA (PerFluoroSulfonic Acid) polymers [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ] because, due to the multivalent oxidation state of the metals, they can act as catalysts for the decomposition of hydroxyl and hydroperoxyl radicals.…”
Section: Introductionmentioning
confidence: 99%